COM571: Personal development / Faculty of Communication and Media Studies - UiTM, Faculty of Communication and Media Studies (2020)
This course is focusing in preparing the students for the challenges of work in the changing job environment. Holistic approach will be imparted in enhancing their personal development by incorporating the components of positive interpersonal skills, self-management, thinking skills, teamwork, ethics, and leadership skills.